FACTORES ASOCIADOS AL TAMIZAJE POSITIVO DE HIPOACUSIA NEUROSENSORIALEN NEONATOS: ESTUDIO DE CASOS Y CONTROLES - Tejeda Pizarro, Jose Eduardo (2026)
Introduction. Neonatal sensorineural hearing loss affects cognitive development. Objectives. To determine the factorsassociated with positive screening for sensorineural hearing loss in neonates at the Instituto Nacional MaternoPerinatal (INMP), Lima, attended between July 2024 and July 2025. Methods. An unmatched case–control study wasconducted. The 51 medical records of all sensorineural hearing loss cases during the study period and 102 controlswere reviewed. The outcome was defined by abnormal otoacoustic emissions and auditory brainstem responses, withvalues greater than 20 dB considered presumptive. Exposures included congenital infections, ototoxic medications,prematurity, neonatal asphyxia, low birth weight (<2500 g), neonatal sepsis, and craniofacial anomalies. Crude andadjusted odds ratios (aORs) and their 95% confidence intervals (95% CIs) were calculated. Results. In the bivariateanalysis, congenital infections (OR=5.65; 95% CI: 2.13–15.00; p=0.001), use of ototoxic medications (OR = 6.44;95% CI: 2.73–15.19; p < 0.001), neonatal asphyxia (OR = 10.98; 95% CI: 1.25–96.65; p = 0.031), low birth weight(OR = 4.18; 95% CI: 2.05–8.52; p < 0.001), and craniofacial anomalies (OR = 6.98; 95% CI: 2.79–17.48; p < 0.001)showed higher odds of sensorineural hearing loss. In the multivariable analysis, independent factors associated withsensorineural hearing loss were low birth weight (aOR = 3.78; 95% CI: 1.49–9.62; p = 0.005) and craniofacial anomalies(aOR = 3.76; 95% CI: 1.26–11.24; p = 0.018). Conclusion. Low birth weight and craniofacial anomalies wereindependently associated with sensorineural hearing loss in neonates at the INMP; therefore, these factors should beprioritized in clinical follow-up.